SCALING RATIO EFFECTS ON THE PREDICTION OF DYNAMIC MOTION OF TENSION LEG PLATFORM PROTOTYPE IN THE VIEW OF TESTING FACILITIES LIMITATIONS - ARANG, JANNET BULAN (IRC, 2016)
The modern technological development has improved engineering field particularly in oil and gas industry with the advanced hydrodynamic models which could be a physical model built to scale especially for the massive floating platforms in the deep water. There are some limitations associate with the virtual numerical modelling for hydrodynamic model as it differs to other computational fluid dynamic specializations for its focus in on the movement of water.